2001
DOI: 10.1016/s0399-1784(00)01129-4
|View full text |Cite
|
Sign up to set email alerts
|

Activity and composition of the benthic fauna in the Whittard Canyon and the adjacent continental slope (NE Atlantic)

Abstract: We compared the sediment and its community on the Celtic continental slope (Goban Spur) with those in a branch of the nearby Whittard Canyon in search for evidence of canyon mediated transport of (labile) organic matter. We studied the megabenthos and macrobenthos biomass and taxonomic composition, measured in situ sediment community oxygen consumption and determined sediment concentrations of particulate organic carbon, phytopigments, and nucleic acids. While the sediment community and activity on the canyon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
76
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 30 publications
(66 reference statements)
6
76
1
Order By: Relevance
“…It funnels organic matter to depth via a variety of mechanisms including tidal currents, internal waves and turbidity flows (Duineveld et al, 2001;Quaresma et al, 2007). The greater hydrodynamic activity in the canyon leads to an increase in organic matter input and increased food quality within the canyon in comparison to less active areas on the open continental slope.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It funnels organic matter to depth via a variety of mechanisms including tidal currents, internal waves and turbidity flows (Duineveld et al, 2001;Quaresma et al, 2007). The greater hydrodynamic activity in the canyon leads to an increase in organic matter input and increased food quality within the canyon in comparison to less active areas on the open continental slope.…”
Section: Discussionmentioning
confidence: 99%
“…The canyon floor is sediment-covered with very little exposed rock, other than on the extreme walls (Reid and Hamilton, 1990). Duineveld et al (2001) found that the POC concentrations were higher in the canyon than in the surrounding open slope areas, indicating organic enrichment within the canyon. The surface waters of the upper reaches of the canyon have relatively high biological productivity because of nutrient upwelling along the Celtic Shelf edge (Wall et al, 2010), resulting in increased nutrient transport through the canyon via mechanisms such as internal wave formation and turbidity flows.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Canyon sediments receive increased POM inputs via both vertical transport, through the water column, and lateral transport, through slope processes. Consequently, canyons may support higher bacterial and faunal densities than surrounding bathyal and abyssal sediments (Vetter and Dayton, 1998;Duineveld et al, 2001;EscobarBriones et al, 2008;De Leo et al, 2010;Cunha et al, 2011). In the Whittard Canyon (Northeast Atlantic), Duineveld et al (2001) report enhanced sediment community oxygen consumption (SCOC) within canyon sediments.…”
Section: Introductionmentioning
confidence: 99%
“…Deep-sea submarine canyons host hotspots of OM and biomass (Gage et al, 1995;Vetter and Dayton, 1998;Duineveld et al, 2001;Bianchelli et al, 2008;Ingels et al, 2009;Tyler et al, 2009;de Leo et al, 2010;Pusceddu et al, 2010;Vetter et al, 2010). Within canyons, biodiversity is high as a result of their topographic complexity and spatio-temporal variability (Bianchelli et al, 2008;Ingels et al, 2009;Tyler et al, 2009;Vetter et al, 2010).…”
Section: Introductionmentioning
confidence: 99%